Tablero de control COVID 19 – AMBA. IDE conurbano. Universidad Nacional de General Sarmiento - Juarez, Andrés (2020)
In the frame of the activity dissemination policy and community service activities carried out by the General Sarmiento National University (UNGS) in general, and in the current scenario of Pandemic of COVID 19, an instrument designed and implemented by the Geographic Information Systems Laboratory of the Geographical Information Technology and Spatial Analysis Area of the Conurbano Institute of this University, is presented. It should be noted that, also following the policy of using open data, this application was made entirely with free software and sources from open repositories, as well as data from the IDE (Spatial Data Infrastructure) of the Conurbano. Declared cases, deaths and discharges produced can be visualized, combined with neighborhoods, popular neighborhoods, critical overcrowding and finally a heat map is also presented